Preservation of δ13C signatures in oak charred wood: Application to the "forest" of Notre-Dame de Paris - Rocha, Eva; Dufraisse, Alexa; Rinne-Garmston, Katja T.; Sahlstedt, Elina; Mendez-Millan, Mercedes; Nguyen Tu, Thanh Thuy; Girardclos, Olivier; Lemoine, Michel; Ghavidel, Amir; Terrei, Lucas; Collin, Anthony; Bellot-Gurlet, Ludovic; et al. (Elsevier, 2025)
The fire of the Notre-Dame de Paris’s cathedral (NDP) in 2019 brought a unique opportunity to study the past environmental conditions in the region during the High Middle Ages through the charred oak beams of the “Forest” (name given to its framework). However, as a preamble, there is a need to evaluate the preservation of the stable carbon isotope signatures (δ13C) in response to changes in molecular composition, occurring with carbonisation. To this end, experimental studies were conducted on modern and NDP oak wood at both inter- and intra-annual levels. Laser ablation was used for the first time on burnt wood. Results show that regardless of the charring duration, at temperatures above 500 °C, carbonisation‑induced 13C fractionation shows a consistent decrease (Δ13C) of approximately 1 ‰ relative to uncharred values. Despite a slight decrease in variance, a strong and significant correlation (rmean = 0.9, p < 0.01) was observed between the uncharred time series and the carbonised counterpart, showing that the C isotopic variability is preserved. This study paves the way to use the charcoal remains from the Notre-Dame de Paris framework as a unique paleoenvironmental archive.
Keywords: carbon isotope; inter- and intra-annual signal; deciduous oak; laser ablation; charcoal; wood